Screening results for retinopathy of prematurity: A retrospective study (Annals of Medical Research, 2024)
Aim: The aim of this study was to determine the frequency of ROP development in premature infants hospitalized in the neonatal intensive care unit and/or referred to the ROP Diagnostic Unit of our hospital and to emphasize the importance of cooperation between ophthalmologists and neonatologists in the treatment and follow-up of infants with ROP.Materials and Methods: The findings of 287 premature infants who were followed and treated in the neonatal intensive care unit between January 2017 and January 2023 and then referred to the ROP Diagnostic Unit were retrospectively analyzed. They were classified according to birth weight and gestational age. They were divided into 4 groups according to birth weight (under 1000 g, between 1000-1250 g, between 1250-1500 g and over 1500 g) and 3 groups according to gestational age (under 28 weeks, between 29-32 weeks and over 33 weeks). ROP development rates were determined in these groups. Those who developed retinopathy of prematurity were classified according to their stages.Results: A total of 287 premature infants (141 boys and 146 girls) were included in the study. Twenty-eight of the premature babies were Syrian (9.8%). Mean gestational age at birth was 32.34 weeks (min. 24, max. 37) and mean birth weight was 1830.12 g (min. 750 g, max. 4000 g). 34 babies (11.8%) had stage 1 ROP and 12 babies (4.1%) had stage 2 ROP. 14 babies (4.9%) had plus. Due to the rapid progression of the clinic, 20 patients (7%) with stage 2 or higher ROP and plus were referred to an advanced center with ROP treatment center certification.Conclusion: Premature babies born under 34 weeks of gestation should be examined for retinopathy of prematurity. Early diagnosis of retinopathy of prematurity is very important to prevent blindness due to ROP, even if treatment is not possible according to local conditions.
Keywords: Retinopathy of prematurity; Neonatology; Prematurity